#
1. (w-6) (w+6) =

2. (a+4c) (a-4c)=

3. (4y-5d) (4y+5d)=

4.(4f+3sd) (4f-3sd)=

5.(12x-3) (12+3)=

1
by emsha

Log in to add a comment

2. (a+4c) (a-4c)=

3. (4y-5d) (4y+5d)=

4.(4f+3sd) (4f-3sd)=

5.(12x-3) (12+3)=

by emsha

Log in to add a comment

=w²-36

2.(a+4c)(a-4c)

=a²-16c²

3.(4y+5d)(4y-5d)

=16y²-25d²

4.(4f+3sd)(4f-3sd)

=16f²-9s²d²

5.(12x-3)(12x+3)

=141x²-9

Explanation: The given factors are sum and difference of two binomials. To get its product, you just have to square the first term and multiply the last terms, and you'll get the special product called difference of two squares.